The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/molecules22040511
|View full text |Cite
|
Sign up to set email alerts
|

Silane Modified Diopside for Improved Interfacial Adhesion and Bioactivity of Composite Scaffolds

Abstract: Diopside (DIOP) was introduced into polyetheretherketone/polyglycolicacid (PEEK/PGA) scaffolds fabricated via selective laser sintering to improve bioactivity. The DIOP surface was then modified using a silane coupling agent, 3-glycidoxypropyltrimethoxysilane (KH570), to reinforce interfacial adhesion. The results showed that the tensile properties and thermal stability of the scaffolds were significantly enhanced. It could be explained that, on the one hand, the hydrophilic group of KH570 formed an organic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…5% of nano‐TiO₂ addition increased the tensile strength to 51 MPa (34% higher than PEEK/PGA), however it dropped with 7% nano‐ TiO₂ addition (41 MPa:32% higher than PEEK/PGA). Finally, they compared the tensile properties of porous PEEK/PGA scaffolds with addition of diopside (DIOP) particles and a silane coupling agent (3‐glycidoxypropyltrimethoxysilane: KH570) along with DIOP (KDIOP) with weight percentages of 0–20% 57 . They showed that tensile strength decreased with addition of DIOP particles (from 38 to 18 MPa with 20% DIOP), whereas it significantly decreased after 10% of KDIOP (38–25 MPa).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5% of nano‐TiO₂ addition increased the tensile strength to 51 MPa (34% higher than PEEK/PGA), however it dropped with 7% nano‐ TiO₂ addition (41 MPa:32% higher than PEEK/PGA). Finally, they compared the tensile properties of porous PEEK/PGA scaffolds with addition of diopside (DIOP) particles and a silane coupling agent (3‐glycidoxypropyltrimethoxysilane: KH570) along with DIOP (KDIOP) with weight percentages of 0–20% 57 . They showed that tensile strength decreased with addition of DIOP particles (from 38 to 18 MPa with 20% DIOP), whereas it significantly decreased after 10% of KDIOP (38–25 MPa).…”
Section: Resultsmentioning
confidence: 99%
“…They concluded scaffolds with 10% HA, provided the optimum outcome and selected for further in vitro testing, promoted cell attachment and proliferation higher than PEEK/PGA scaffolds without HA. Furthermore, they added DIOP (a calcium magnesium silicate bioceramic) and KDIOP (silane modified DIOP) into SLS PEEK/PGA scaffolds with different weight percentages 57 . They indicated cell viability was significantly higher with 10% KDIOP addition to PEEK/PGA scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…SLS relies on a laser beam to transform powdered particles into a three-dimensional solid by applying heat locally [104]. Several biocompatible polymers like PCL [105,106], poly (L-lactic acid) (PLLA) [107], polyether ether ketone (PEEK) [108,109], polyvinylidene fluoride (PVDF) [110] and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) [111] can be used either as single ingredients or as hybrid composites. Bioceramics can be incorporated to improve bioactivity [111,112] and/or the construct mechanical properties [113,114].…”
Section: (C) Three-dimensional Printingmentioning
confidence: 99%
“…11 It is believed that their degradation products are lactic acid and glycolic acid. 12 Both the products are considered as part of various metabolic pathways under normal physiological conditions in the human body. 13 Recently, PLLA in combination with other natural polymers has been used as a promising wound dressing matrix.…”
Section: Introductionmentioning
confidence: 99%